Pengaruh Kompensasi dan Sosial Support Terhadap Turnover Intention Pada SMP Maitreyawira Palembang - Nurhalizah; Purnamasari, Endah Dewi; Lazuarni, Shafiera (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine whether compensation and social support have an effect on employee turnover intention at SMP Meitreyawira Palembang. The type of research in this study is quantitative research. The data collection technique in this study is a questionnaire. The population and sample in this study were 75 respondents. The data analysis technique in this study used validity tests, reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests, multiple regression analysis tests, hypothesis tests consisting of t tests, f tests and coefficients of determination. The results of the data analysis showed that there was a significant influence between the independent variables, namely compensation and social support, on the dependent variable, namely turnover intention, this was indicated by the t-count value of compensation of -3.347> t-table value of 1.993 with a significance value of 0.001 <0.05 and the t-count value of social support of -3.823> 1.993 with a significance value of 0.000 <0.05. This means that the hypothesis proposed in this study is that the compensation variable has a negative and significant effect on turnover intention. The social support variable has a negative and significant effect on turnover intention. The magnitude of the influence of the compensation and social support variables is 57.2% on turnover intention. While the remaining 42.8% is influenced by other variables such as work stress and workload which were not examined in this study.